A dynamic programming algorithm for identification of triplex-forming sequences - Lexa, Matej; Martínek, Tomáš; Burgetová, Ivana; Kopeček, Daniel; Brázdová, Marie (Bioinformatics, 2011)
Motivation: Current methods for identification of potential triplex-forming sequences in genomes and similar sequence sets rely primarily on detecting homopurine and homopyrimidine tracts. Procedures capable of detecting sequences supporting imperfect, but structurally feasible intramolecular triplex structures are needed for better sequence analysis. Results: We modified an algorithm for detection of approximate palindromes, so as to account for the special nature of triplex DNA structures. From available literature, we conclude that approximate triplexes tolerate two classes of errors. One, analogical to mismatches in duplex DNA, involves nucleotides in triplets that do not readily form Hoogsteen bonds. The other class involves geometrically incompatible neighboring triplets hindering proper alignment of strands for optimal hydrogen bonding and stacking. We tested the statistical properties of the algorithm, as well as its correctness when confronted with known triplex sequences. The proposed algorithm satisfactorily detects sequences with intramolecular triplex-forming potential. Its complexity is directly comparable to palindrome searching. Availability: Our implementation of the algorithm is available at http://www.fi.muni.cz/lexa/triplex as source code and a web-based search tool. The source code compiles into a library providing searching capability to other programs, as well as into a stand-alone command-line application based on this library. Contact:  lexa@fi.muni.cz Supplementary Information:  Supplementary data are available at Bioinformatics online.